Inventory Planning in The Supply Chain Network of Sunflower Agro-Industry - Nurhasanah, Nunung Nurhasanah; Putri, Hani Adinda; Noviyanti, Anissa; Riyana, Tharra Azzahra; Aribowo, Budi; Haryadi, Dody; Sudarwati, Wiwik (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2025)
Sunflower agro-industry can potentially be a raw material for vegetable oil from seeds. In Indonesia, sunflower is a vegetable oil that is produced very limitedly. However, inventory planning is needed in the sunflower agro-industry's supply chain system to maximize this potential. At the same time, the sunflower agro-industry does not yet have a formal production and inventory planning system. Production activities are carried out based on the owner's intuition or orders received by the marketing department. The sunflower agro-industry supply chains consist of upstream, midstream, and downstream, but this research focused on the upstream and midstream segments. The upstream supply chain consists of sunflower seeds. Meanwhile, the midstream supply chain consists of sunflower cooking oil with 250 ml, 500 ml, and 1 liter packaging. This research aims to design the inventory planning by determining the economic order quantity using the single order quantity (SOQ) method, safety stock, number of orders, and reorder points. The results obtained in this study are the economic order, number of safety stock, number of orders, reorder points, and reorder points graph for sunflower agro-industry supply chains in 6 months. The upstream stage exhibits higher inventory requirements compared to the midstream. This may be caused by the need to buffer against higher variability in raw material availability. While the midstream inventory planning focuses on maintaining minimal safety stock due to predictable demand.